Pengaruh Konsentrasi Gelatin Tulang Ikan Bandeng (Chanos chans F.) Pada Pembuatan Permen Jelly dari Bunga Rosella (Hisbiscus sabdariffa L.) - Irash, Nur Faizun; Supriadi, Supriadi; Suherman, Suherman (Jurnal Akademika Kimia, 2018)
Rosella is one of the plants that has many benefits as well as nutrients used potentially as food ingredients such as jelly candy. Jelly candy was made by mixing rosella flower extracts with a gelling agent. This study aimed to determine the effect of the addition of gelatin from milkfish bones toward the production of jelly from rosella flowers and to determine the addition concentration of gelatin from milkfish bones to obtain a good quality of jelly candy. The gelling agent used was gelatin derived from milkfish bones. Gelatin from milkfish bones was made through several stages i.e. degreasing, demineralization, extraction, and drying then applied to produce jelly candy. Rosella flower was extracted using the infusion method at a temperature of 70 oC. The addition concentration of gelatin varied of 10, 12, 14, 16 18, and 20%. Parameters used were water content and organoleptic test covering of color, aroma, flavor, and texture. Results showed that addition of gelatin from milkfish bones influenced strongly on the moisture content, color, aroma, flavor, and texture of the jelly candy. The good quality of rosella jelly candy was obtained by addition concentration of gelatin of 18% with a water content of 8.76%, and the elasticity was preferred by the panelists.